The formation of ZnO nanoparticles from zinc gluconate. Issue 3 (April 2015) - Petrović, Željka; Ristić, Mira; Musić, Svetozar; Sepiol, Bogdan; Peterlik, Herwig
Abstract: A simple and reproducible procedure for the preparation of ZnO nanoparticles is presented. It is based on the alkali precipitation from zinc gluconate solution, followed by ageing the precipitation systems at room temperature for a period between 1 and 60 days and calcination of isolated precipitates at 300 °C. The crystallites of all ZnO samples were in the nanosize range as determined by the Scherrer method. There were no significant texture effects, which indicates the lack of a preferential ZnO crystallite orientation. XRD showed the amorphous nature of zinc (hydrous)oxide precursors. SAXS analysis of a zinc (hydrous)oxide precursor showed the presence of structural units at the mean distance of 1.5 nm. This is attributed to the typical distance of the adsorbed gluconate groups. The adsorption of gluconate groups on the zinc (hydrous)oxide precursor was confirmed by FT-IR spectroscopy. FE-SEM images showed a gradual aggregation of ZnO nanoparticles with the prolonged ageing time of the amorphous zinc (hydrous)oxide suspension. Optical spectra were recorded and the band gap gradually decreased from 3.25 eV to 3.05 eV for ZnO samples produced from initially precipitated suspensions aged between 1 and 60 days.